THE RELATIONSHIP OF ENGLISH LANGUAGE USAGE SKILLS, ENGLISH READING PROFICIENCY AND ENGLISH SELF-EFFICACY WITH MATHEMATICS ACADEMIC ACHIEVEMENT OF GRADES 3-4 AND GRADES 5-6 STUDENTS AT PAN-ASIA INTERNATIONAL SCHOOL, BANGKOK, THAILAND - BALCI, MUSTAFA; LYNCH, RICHARD (Scholar: Human Sciences, 2022)
This quantitative correlational study aimed to investigate whether there was a significant relationship of English language usage skills, English reading proficiency and English self-efficacy with mathematics academic achievement of Grades 3-4 and Grades 5-6 students at Pan-Asia International School Bangkok, Thailand, at a significance level of .05. This research was conducted among 39 Grades 3-4 students and 49 Grades 5-6 students who were enrolled in the academic year 2019 - 2020. In order to determine the students’ level of English language usage skills, English reading proficiency and mathematics academic achievement, the Measure of Academic Progress (MAP) Tests scores were used. The second research instrument was the Questionnaire of English Self-Efficacy (QESE; Wang et al., 2013) which was used to measure the students’ English self-efficacy level. Descriptive statistics (means and standard deviations) and correlational analysis (using multiple correlation coefficient) were applied to analyse the relationship between the independent variables (English language usage skills, English reading proficiency and English self-efficacy) and the dependent variable (mathematics academic achievement). According to the research findings, the results of Grades 3-4 and Grade 5-6 students were below the student achievement norm levels in English language usage, English reading and mathematics, which were determined and provided by Northwest Evaluation Association (NWEA). Grades 3-4 and Grades 5-6 students’ perceived self-efficacy in English were moderately high. The correlational analysis revealed that the mathematics academic achievement of Grades 3-4 students was positively, significantly and very strongly correlated with their English language usage skills, English reading proficiency and English self-efficacy. It also indicated that there was a positive, significant, strong multiple correlation among English language usage skills, English reading proficiency, English self-efficacy and mathematics academic achievement of Grade 5-6 students.